Malignant pleural mesothelioma - Neumann, Volker; Löseke, Stefan; Nowak, Dennis; Herth, Felix; Tannapfel, Andrea (Deutsches Ärzteblatt, 2013)
Malignant diffuse mesothelioma is a tumor arising from the mesothelial or submesothelial cells of the pleura, peritoneum, or pericardium. More than 80% of all mesotheliomas originate in the pleura (1), and more than 80% of patients with pleural...
Das PDF enthält zusätzlich einen Anhang von 3 Seiten
Gesehen am 06.12.2021